Qualitative analysis of topical corticosteroid concerns, topical steroid addiction and withdrawal in dermatological patients. Issue 3 (16th March 2022) - Tan, Sean; Phan, Phillip; Law, Je Yin; Choi, Ellie; Chandran, Nisha Suyien
Abstract : Objective: To explore the phenomenon of topical corticosteroid (TCS) phobia and comprehensively understand the factors driving TCS concerns, in particular pertaining to steroid addiction and withdrawal. Design: Prospective qualitative study using 1:1 in-depth semistructured interviews and analysed using grounded theory. Participants: Patients with a prior experience of TCS use for a dermatological condition recruited from a tertiary academic dermatology clinic, or through word of mouth and online social media platforms. Results: 26 participants encompassing those with positive, neutral and negative opinions towards TCS were interviewed. 13 reported having topical steroid addiction or withdrawal. The drivers of TCS concerns could be categorised into seven themes: attitudes towards TCS (comprising beliefs and knowledge about TCS), availability of alternatives, treatment inconvenience, personality, patient's ongoing evaluation of clinical response to TCS, doctor–patient relationship and healthcare-seeking behaviour. Of mention, patients placed high value and trust on their own experiences with TCS, such as their perceived experienced side effects. The doctor who failed to acknowledge the patient's opinions and instead emphasised the safety of TCS was often viewed as dismissive, resulting in a deteriorating patient–doctor relationship. Conclusion: Provision of knowledge and education is important but may be ineffective if the basis for TCS concern regarding safety is reasonable, or when the patient has a firmly established belief supporting his/her concern. In such instances, failure to acknowledge and respect the patient's decision to avoid TCS could worsen the doctor–patient relationship.